2005
DOI: 10.1210/jc.2004-1588
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association between Serum Hepatocyte Growth Factor and Metabolic Syndrome

Abstract: Hepatocyte growth factor (HGF) is one of the adipocytokines. We evaluated whether serum levels of HGF are related to the metabolic syndrome. A total of 1474 subjects of a general population free of liver, kidney, and lung diseases received a health examination. We measured blood pressure, waist circumference, body mass index, fasting plasma glucose, lipid profiles, serum insulin, liver enzymes, and HGF concentrations. Uni- and multivariate analyses for determinant of HGF were performed. In univariate analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 18 publications
3
51
2
3
Order By: Relevance
“…HGF release into the culture medium was quantitated by ELISA. *P ϭ 0.02. recent large study of Japanese men and women, serum HGF was strongly associated with metabolic syndrome independently from liver function (10). Taken together, these studies suggest that elevated serum HGF in obesity may contribute to the development of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…HGF release into the culture medium was quantitated by ELISA. *P ϭ 0.02. recent large study of Japanese men and women, serum HGF was strongly associated with metabolic syndrome independently from liver function (10). Taken together, these studies suggest that elevated serum HGF in obesity may contribute to the development of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 60%
“…More recently, the role of HGF in cardiovascular disease has been reemphasized by the fact that high circulating levels of HGF in patients with coronary artery disease predict a greater long-term risk of atherothrombotic events following percutaneous coronary revascularization (29). Furthermore, Hiratsuka et al (10) found that serum HGF levels are strongly associated with components of the metabolic syndrome in individuals free of liver and kidney disease. Taken together, these observations and others implicate HGF in the development of cardiovascular disease and cancer.…”
mentioning
confidence: 99%
“…On the other hand weight loss after gastroplasty has been shown to be associated with a reduction of HGF plasma levels in obese patients (12,14). A strong association between elevated serum HGF and metabolic syndrome has also been reported (15).…”
mentioning
confidence: 98%
“…Furthermore, HGF levels have been reported to be elevated in obese patients and raised with body mass index (6 -10). On the other hand, weight loss after gastroplasty has been shown to be associated with a reduction of HGF plasma levels in obese patients (6). A strong association between elevated serum HGF and metabolic syndrome has also been reported (6 -10).…”
mentioning
confidence: 99%